Perfil epidemiológico de crianças e adolescentes portadores de neoplasias acompanhados no Hospital de Câncer de Mato Grosso - Araújo, Suely Santos (2014)
The pediatric cancer represents about 3% of all malignant tumors diagnosed worldwide, and over 160,000 cases per year. In 2014, it is estimated that will occur in Brazil about 11,840 new cases of cancer in children and adolescents below 19 years of age. Objective: To describe the epidemiology of malignancies in children and adolescents followed in Cancer Hospital of Mato Grosso. Method: This is a retrospective cohort of patients diagnosed with cancer in the period 2002-2012, using information from the medical records of the institution. Results: 658 cases of malignancies were analyzed, most were without previous cancer treatment (73.70%), the most common signs and symptoms were fever, pain and pallor, 43.44% had a family history of cancer. Most occurred in males, most evident in adolescents (59.14%). The mean age of the children at the first consult was 4.82 years and for the adolescents was 14.38 years. The black race predominated in the adolescents, and white color predominated in the children group. The majority of maternal and paternal education was uncompleted basic school and most families had per capita monthly family income below the Brazilian poverty line. Whereas 0-19 years, the most frequent diagnostic groups were leukemias (36.32%), lymphomas and reticuloendothelial neoplasms (16.87%) and tumors of the central nervous system and miscellaneous intracranial and intraspinal neoplasms (11.40%), similar distribution occurred in children but in adolescents, the third group was more frequent diagnosis of bone tumors. In the white race, the most frequent diagnostic groups were leukemias, lymphomas and soft tissue sarcomas and in the black race were leukemias, lymphomas and reticuloendothelial neoplasms and tumors of the central nervous system and soft tissue sarcomas. The most frequent diagnosis groups in both sexes were leukemias, lymphomas, and cancers and tumors of the reticuloendothelial and central nervous system and soft tissue sarcomas. The majority (64.33%) of cases was coming from three health regions of Mato Grosso: Baixada Cuiabana, Rondonópolis and Sinop. The median of time interval between the first symptoms and the first consultation was 48.50 days, between the first symptoms and diagnosis was 43.0 days, between the date of first symptoms and beginning of treatment was 51 days. Excluding the cases of malignancy with a diagnosis or who received previous oncological treatment, the median of time interval between the first consultation and diagnosis was 5.0 days and between the date of diagnosis and start of treatment was 5.0 days. The majority (80.59%) of the cases analyzed showed no recurrence during the follow-up period. At the end of the study period, the majority (56.62%) cases of malignancies were alive without cancer and 34.70% died with cancer. Conclusions: The sociodemographic characteristics and distribution of the most frequent diagnostic groups were similar to the pattern of Brazilian and world literature. Most had family monthly per capita income below the poverty line which shows the important social role of the Cancer Hospital of Mato Grosso to the attended population.